2017
DOI: 10.1177/0117196817746429
|View full text |Cite
|
Sign up to set email alerts
|

Reality or pretense? Renouncing nationality and organized hypocrisy of the sovereignty of Taiwan

Abstract: Adopting Krasner's thesis of organized hypocrisy, this research examined the institution of sovereignty in regard to the naturalization of migrant spouses in Taiwan. Using migrant spouses as a case study, this article argues that the hypocrisy of Taiwan's sovereignty lies in demanding migrants to renounce their native nationality or cancel their household registration. This demand not only fails to prevent statelessness but also prompts the origin state to recognize or reject Taiwan's sovereignty. The interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It is estimated that the number of mainland sol-diers who moved to Taiwan between 1945 and 1953 amounted to approximately 600,000 in total (Lin 2009: 333-36). Though native Taiwanese men were conscripted into the army after 1949, mainland soldiers were professional servicemen and constituted the main force in various military attacks on China in the 1950s and 1960s (Cheng 2018). The KMT's policies regarding military brothels and soldiers' marriages specifi cally targeted these mainland soldiers whose military morale was essential to the KMT's anti-communist struggle.…”
Section: State Control Of Soldiers' Sexuality and Marriagementioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that the number of mainland sol-diers who moved to Taiwan between 1945 and 1953 amounted to approximately 600,000 in total (Lin 2009: 333-36). Though native Taiwanese men were conscripted into the army after 1949, mainland soldiers were professional servicemen and constituted the main force in various military attacks on China in the 1950s and 1960s (Cheng 2018). The KMT's policies regarding military brothels and soldiers' marriages specifi cally targeted these mainland soldiers whose military morale was essential to the KMT's anti-communist struggle.…”
Section: State Control Of Soldiers' Sexuality and Marriagementioning
confidence: 99%
“…This entanglement between border and boundary is palpable in the Taiwanese government's different treatment of spouses originally from China and those from other countries. As several studies have shown, due to Taiwan's special relationship with China, the Taiwanese government's policies of pre-entry interview, residency and citizenship for Chinese spouses are different from those for spouses from other countries (Cheng 2017;Friedman 2010bFriedman , 2015Lan 2008;Momesso and Cheng 2017). Friedman's (2010bFriedman's ( , 2015 work, especially, pertinently captures the interrelated anxieties of the Taiwanese state's exercise of sovereignty and dealing with Chinese spouses' 'similarity' to Taiwanese citizens through differentiated legal and political treatment.…”
Section: Border-crossing and Reconnecting Kinmentioning
confidence: 99%
See 1 more Smart Citation